A general ethnographic survey of the amaBhaca (East Griqualand) - Hammond-Tooke, William David (Social Anthropology, 2016)
The material for this survey was collected during field investigations in the Mount Frere district of East Griqualand during the period January to October, 1949. The Bhaca are a small group of people occupying roughly the district of Mount Frere - although a considerable number lie outside district boundaries, particularly on the Mount Ayliff side - with a Southern Nguni type of culture and speaking a dialect of Xhosa. They are of particular interest as they are representative of those tribes who were forced to flee from Natal during the chaotic period of Zulu history subsequent to T/haka's rise to power, and, unlike the Mpondo, Thembu and Xhosa tribes, they are thus fairly recent immigrants into the Cape. The Bhaca are very conscious of their Zulu origin, although "Zulu" is hardly the scientifically correct term to apply to it. Van Warmelo has stressed the fact that before the rise of T/haka (c 1816) Natal was the home of a number of different tribes, the majority little more than large clans, roughly divisible into separate groups both dialectically and culturally, viz., (a) the true Nguni or Ntungwa, (b) the Mbo and (c) the Lala tribes. The name "Zulu" should correctly be applied only to the descendants of the small Zulu clan which by rapine and conquest established political and cultural supremacy over the whole of Natal from 1816 onwards. Those tribes which did not submit were forced to flee or be annihilated, and these successive southward waves of fugitives have given rise to the establishment of numerous small tribes in the Cape, classified by van Warmelo as "Fingo and Other recent Immigrants into the Cape". Other tribal elements moved north and today exists as Swazi, Rhodesian Ndebele, Transvaal Ndebele, Ngani and others. At least a century of wandering away from Natal has modified considerably the culture of these immigrants and today the culture of Bhaca, Xesibe (in the district of Mount Ayliff) and the various Mfengu tribes, approximates more nearly to Southern Nguni than to Northern Nguni culture. Foreign influence on the Bhaca must have been strong - at one period the tribe lived in Pondoland under the protection of Faku - and today there is intermarriage with Mpondo, especially on the Eastern boundary which impinges on the district of Tabankulu, and with Hlubi and Xesibe. In the following chapters the question or cultural origins and ethnic composition will be taken up: here it is sufficient to say that ethnographically Bhaca culture today is southern Nguni in character.